2020
DOI: 10.3390/nu12102993
|View full text |Cite
|
Sign up to set email alerts
|

Significant Decreased Expressions of CaN, VEGF, SLC39A6 and SFRP1 in MDA-MB-231 Xenograft Breast Tumor Mice Treated with Moringa oleifera Leaves and Seed Residue (MOLSr) Extracts

Abstract: Moringa oleifera is a miracle plant with many nutritional and medicinal properties. Chemopreventive values of the combined mixture of moringa leaves and seed residue (MOLSr) at different ratios (M1S9, M1S1 and M9S1) were investigated. MOLSr extracts were subjected to phytochemical screening, antioxidant assays, metabolite profiling and cytotoxic activity on the primary mammary epithelial cells (PMECs), non-malignant Chang’s liver cells and various human cancer cell lines (including breast, cervical, colon and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…In addition to ADCs targeting ZIP6, a few small molecules have been reported. For instance, M9S1 extracted from Moringa oleifera significantly downregulated the expression of ZIP6 in MDA-MB-231 tumor, 602 treatment with STAT3 inhibitor peptide, cell-permeable (#573096, Sigma). Besides, the antiestrogens (Faslodex and 4‐hydroxytamoxifen, each 100 nM) also indicated that the expression of LIV-1 was decreased in MCF7 cells.…”
Section: Therapeutic Targets For Cellular Zinc Metabolismmentioning
confidence: 99%
“…In addition to ADCs targeting ZIP6, a few small molecules have been reported. For instance, M9S1 extracted from Moringa oleifera significantly downregulated the expression of ZIP6 in MDA-MB-231 tumor, 602 treatment with STAT3 inhibitor peptide, cell-permeable (#573096, Sigma). Besides, the antiestrogens (Faslodex and 4‐hydroxytamoxifen, each 100 nM) also indicated that the expression of LIV-1 was decreased in MCF7 cells.…”
Section: Therapeutic Targets For Cellular Zinc Metabolismmentioning
confidence: 99%
“…The selected genetic materials, in order of the number of accessions, originated from Malaysia (5), Thailand (5), Taiwan (4), Vietnam (2), China (2), Mauritius (2), India (1), Laos (1), and Bangladesh (1). With regard to their biological status, they were segregated as landraces (17) and cultivars (6) (Table 1).…”
Section: Choy Sum Genetic Materials and Cultivation Conditionmentioning
confidence: 99%
“…italic ), etc., and are representative secondary metabolites of plants that also play a role in protecting plants from attacks by viruses or pests [ 12 , 13 , 14 , 15 ]. In terms of their value to humans, glucosinolates are potential compounds that have been well established for their anti-cancer as well as antioxidant functions [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moringa oleifera (MO) is a traditional medicinal tree belonging to the Moringaceae family which has shown great potential as complementary and alternate medicine in cancer [178]. Emerging evidence highlighted the anti-inflammatory, antioxidant, antimicrobial, apoptotic and antiproliferative effects of MO in vitro and in vivo [179][180][181]. Consistently, MO up-regulated some pro-apoptotic proteins such as Bax, p21, and p53 whereas modulated nuclear translocation of NF-κB in cancer cells in a concentration-and time-dependent manner [179].…”
Section: Moringa Oleiferamentioning
confidence: 99%